Assessing the effects of water flow patterns on dam construction in degraded tropical peatlands - Adi Jaya; Franssico H.R.H. Baru; Alderina Rosalia Nahan; Salampak Dohong (Journal of Degraded and Mining Lands Management, 2022)
Tropical peat swamp forest becomes degraded through forest removal and drainage, usually followed by land use change and fire. Restoration of the degraded peatland requires rewetting, which involves canal blocking and water level management. The purpose of canal blocking is to rewet the peat so that peat-forming trees can re-establish or crops be grown with minimal greenhouse gas emissions and peat subsidence. In addition, wet peat is more fire resistant than degraded dry peat. Canal construction faces several technical problems, including stress that causes bending, water seepage under the dam, and erosion of peat by water forcing its way around the sides when the water level upstream exceeds the dam height. This research examined the behaviour of water flows in canals in peatland in Central Kalimantan after blocking with dams of different designs. This study used a survey method and hydraulic physical model test with a horizontal scale of 1:30 and a vertical scale of 1:10. Field measurements were carried out on the primary canal of the former Mega Rice Project (MRP) Block C to build a physical model test prototype for laboratory research, includes measurement of cross-sections, canal length and water flow for a distance of 100 metres upstream and downstream of the construction. The test included three types of the physical model, reviewed for the effect of flow patterns caused by flood discharge frequencies of 5, 25, 50 and 100 years. The effects of flow patterns on canal dam construction in peatland were obtained from the physical model test.